If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -7) * 7 = 6x + -6 Reorder the terms: (-7 + x) * 7 = 6x + -6 Reorder the terms for easier multiplication: 7(-7 + x) = 6x + -6 (-7 * 7 + x * 7) = 6x + -6 (-49 + 7x) = 6x + -6 Reorder the terms: -49 + 7x = -6 + 6x Solving -49 + 7x = -6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -49 + 7x + -6x = -6 + 6x + -6x Combine like terms: 7x + -6x = 1x -49 + 1x = -6 + 6x + -6x Combine like terms: 6x + -6x = 0 -49 + 1x = -6 + 0 -49 + 1x = -6 Add '49' to each side of the equation. -49 + 49 + 1x = -6 + 49 Combine like terms: -49 + 49 = 0 0 + 1x = -6 + 49 1x = -6 + 49 Combine like terms: -6 + 49 = 43 1x = 43 Divide each side by '1'. x = 43 Simplifying x = 43
| 2(4x-1)=3(x+2)+5 | | f(-4)=4x-2 | | 65327=.8x | | c=24n+4 | | 6(x-11)=15-14x | | 6x+6x+2+7=4x+5+7x | | 3x-1/x-4 | | 460=24n+4 | | 6y-2(y+1)=(y-2)+6 | | 7x+11=3(x+y) | | (3d)(3d)(d-7)=0 | | X+(X*0.75)=608 | | 5(x-4)-(12-x)=11+6(1+x) | | 28b-21/7 | | 78=15+21b | | (4z-1)(3-z)=0 | | f(x)=x^6+7x^3-8 | | (11b-3)-5(2b+2)=-3 | | X/7=7/6 | | -130=5(6m+5)+m | | 4x+59-63=12 | | 13=a+2 | | -5(3b+1)+(16b-1)=0 | | -155=31m | | 2x+4*2=2*(x+2) | | Z/5=4/3 | | 4x+6=7x+3(2-x) | | [10-20]-[-7]= | | 130=31m+25 | | 5.12-3.34x=2x-1.555 | | Log[3](-7-4x)=1 | | 5x+8x+11=180 |